Hubungan Produktivitas Lahan dan Pendapatan pada Usahatani Cengkeh di Desa Waode Buri Kecamatan Kulisusu Utara Kabupaten Buton Utara - Hamiza, Hamiza; Taridala, Sitti Aida Adha; Abdullah, Weka Gusmiarty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aims to know the productivity of clove farming, to know the income of loving farming, to analyze the relationship of land productivity and clove farm income in Waode Buri Village North Kulisusu Sub-District North Buton District. The population in this research is all clove farmers in Waode Buri Village North Kulisusu Sub-District North Buton District which is clove farm and has no work outside of farming which is 70 farmers. The sampling technique in this study was conducted by the census (Saturated Sampling), thus the number of clove farmer sample as much as 70 farmers. The results of this study showed that the average productivity of clove farming in Waode Buri Village North Kulisusu Sub-DistrictNorth Buton District is 0.29 ton/ha. The average income of clove farming in Waode Buri Village North Kulisusu Sub-District North Buton District is Rp 13,305,338.36/ha/year. The relationship between the two variables of land productivity and income on clove farming in Waode Buri Village North Kulisusu Sub-District North Buton District has strong correlation coefficient value because of r > 0,5. North Buton District has strong correlation coefficient value because of r> 0,5.